Pengaruh Pemberian Pakan Berbeda Terhadap Pertumbuhan Ikan Betutu (Oxyeleotris marmorata. Blkr.) dalam Jaring Hapa - Syaiful Ramadhan Harahap; Andi Yusapri (Berkala Perikanan Terubuk, 2015)
The influence of natural feed alternative on the growth of sand goby, Oxyeleotris marmorata (Blkr.), in hapa nets were evaluated in this research. This research purposed to determine shrimp trash and fish trash towards specific growth rate, daily length growth rate and daily feed in take for sand goby. This research was carried out at the Teluk Dalam villages, district of  Indragiri Hilir. Completely randomized design was used in this research with two treatments: fish trash and shrimp trash with three replications. The fish were fed of 30% (wet weight based) of total body weight in two time of feeding (10:00, 14:00 WIB) with ad libitum. The amount of feed was adjusted every 14 days with sampling. Provision ofnatural feed alternative has an influence on the specific growth rate, daily length growth rate and daily feed  in take. The sand goby feeding with fish trash showed better specific growth rate and daily length growth rate than those shrimp trash. Daily feed intake with shrimp trash better than those fish trash.These results indicate that the trash fish have a higher nutrient content than those shrimp trash that used during the study